Ultrasound-triggered enzymatic gelation - Nele,V; Schutt,CE; Wojciechowski,J; Kit-Anan,W; Doutch,JJ; Armstrong,J; Stevens,M (Advanced Materials, 2020)
Hydrogels are formed using various triggers, including light irradiation, pH adjustment, heating,cooling or chemical addition. In this report, a new method for forming hydrogels is introduced:ultrasound-triggered enzymatic gelation. Specifically, ultrasound is used as a stimulus to liberateliposomal calcium ions, which then trigger the enzymatic activity of transglutaminase. Theactivated enzyme catalyzes the formation of fibrinogen hydrogels through covalent intermolecularcrosslinking. The catalysis and gelation processes are monitored in real time and both the enzymekinetics and final hydrogel properties are controlled by varying the initial ultrasound exposure time.This technology is extended to microbubble-liposome conjugates, which exhibit a stronger responseto the applied acoustic field and are also used for ultrasound-triggered enzymatic hydrogelation. Tothe best of our knowledge, these results are the first instance in which ultrasound has been used as atrigger for either enzyme catalysis or enzymatic hydrogelation. This approach is highly versatile and Peer reviewed version of the manuscript published in final form at Advanced Materials (2020)2could be readily applied to different ion-dependent enzymes or gelation systems. Moreover, thiswork paves the way for the use of ultrasound as a remote trigger for in vivo hydrogelation.